RETRACTED: Scientific concept of intelligent cyber-physical technopolis - Shkarupeta Elena; Babkin Aleksandr; Rodionova Valentina; Shchegoleva Tatiana; Smolyaninova Irina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001